2022
DOI: 10.1021/acssuschemeng.1c08592
|View full text |Cite
|
Sign up to set email alerts
|

Unique Lysine-Rich Sequence on the CYT Domain of AfCDH Enhances Its Interdomain Electron Transfer and Activation of AA9 LPMOs

Abstract: Cellobiose dehydrogenase (CDH) is a biologically relevant electron donor for lytic polysaccharide monooxygenase (LPMO) in the oxidative cleavage of recalcitrant polysaccharides, so exploring the intrinsic factors affecting the electron transfer from CDH to LPMO is vital for governing the CDH-driven LPMO reaction efficiency. We previously found a unique lysine-rich sequence on the cytochrome (CYT) domain of Af CDH from Aspergillus fumigatus. Here, we comprehensively compared the functionality of Af CDH and Af C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In other words, LPMO might uniquely harness the extracellular redox network with temporal and spatial precisions to specifically target lignin or carbohydrate at different stages of biomass degradation to maximize the efficiency. In the context of extracellular redox network, LPMO could be activated by direct accepting electrons from CDH 14 and some small molecular reductants like diphenols 1 and ascorbic acid 3 to carry out oxidation reactions. When activating in absence of cellulose, LPMO could produce H 2 O 2 by recruiting O 2 and accepting electron from the donors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, LPMO might uniquely harness the extracellular redox network with temporal and spatial precisions to specifically target lignin or carbohydrate at different stages of biomass degradation to maximize the efficiency. In the context of extracellular redox network, LPMO could be activated by direct accepting electrons from CDH 14 and some small molecular reductants like diphenols 1 and ascorbic acid 3 to carry out oxidation reactions. When activating in absence of cellulose, LPMO could produce H 2 O 2 by recruiting O 2 and accepting electron from the donors.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Recent breakthroughs expanded the substrates of LPMO and discovered the oxidative activities of LPMOs on all major polysaccharides, including cellulose, 4 , 5 hemicellulose, 6 , 7 , 8 chitin, 3 , 9 and starch. 10 Current studies also suggested that LPMOs oxidized carbohydrate through recruiting oxygen to copper active site 11 , 12 , 13 and accepting electrons from a variety of external electron donors, including cellobiose dehydrogenase (CDH), 14 photosynthetic pigment, 15 and small molecular reductants. 1 , 3 , 5 , 16 , 17 Despite the progresses, it is still unclear if LPMOs oxidize the substrates beyond the carbohydrates in lignocellulose.…”
Section: Introductionmentioning
confidence: 99%